Stability enhancement of a wind plant based on a DFIG and a PMSM: A Lyapunov approach - A. Bennouk; A. Nejmi; M. Ramzi (Energy Reports, 2018)
This paper presents a hybrid wind generation with a doubly-fed induction generator (DFIG) and a permanent magnet synchronous machine (PMSM). The study analyzes the performances of the two wind systems and assets the stability of the operating parameters in the presence of a grid fault. Both the DFIG and PMSM Machine-Side Converter (MSC) nonlinear commands are built according to Lyapunov conditions, while the Grid-Side Converter (GSC) command is based on a standard vector control. In the first stage, the control of a 1.5 MW DFIG is presented. Then, the hybrid system including the two wind turbines is presented. Stability performances analysis is based on the verification of the standard operating parameters. The simulation is carried under Matlab/Simulink.
Keywords: 330; DFIG; GSC; Lyapunov; MPPT; MSC; PMSM; Transmission grid; Wind turbine